Investigating determinants of entrepreneurial intentions among accounting students - Banda, S. (FMLIC - Conference Proceedings, 2024)
Entrepreneurship is a prerequisite for sustainable development and the resolution of the unemployment crisis. Resultantly, there is a significant shift towards cultivating an entrepreneurial mindset in graduates. Despite the integration of entrepreneurial content into the curriculum, the unemployment rate in South Africa continues to increase sharply. In the second quarter of 2024, the unemployment rate was at an overwhelming rate of 33.5%. Also, the number of unemployed university graduates including those in accounting is intensifying. It is evident that universities should shift from producing job-seeking graduates to entrepreneurial graduates. This study investigates the determinants of entrepreneurial intentions among accounting students. It seeks to examine how the effects of the Bachelor of Accountancy (Chartered Accountancy) curriculum and mentoring programs on entrepreneurial intentions when mediated by attitude, perceived behavioural control and subjective norms. A quantitative approach was employed and similar to extant literature, data was collected using a Likert scale questionnaire. The survey was administered to 163 accounting students in their final year of study at an institution of higher education in South Africa. The collected data was analysed using factor analysis to assess the validity and reliability of constructs. Thereafter, Structural Equation Modelling (SEM) was applied to examine the relationship between variables and identify key determinants of entrepreneurial intention. Results indicate that entrepreneurial pedagogy has a significant association with student attitudes and self-confidence. Furthermore, attitude and perceived behavioural control have a moderately positive influence on entrepreneurial intentions. These insights suggest that students with strong entrepreneurial attitude and confidence in their abilities are predisposed to engage in entrepreneurial activities. Conversely, mentorship support and subjective norms have a weak correlation though they may indirectly influence student attitudes. These results emphasise the role of an enabling environment and curriculum which supports the development of an entrepreneurial mindset. The study propose that universities should strengthen their mentoring programs to leverage their potential to further influence student attitudes and confidence. Future research could explore a longitudinal approach to examine entrepreneurial intention over time, include a more diverse sample for greater generalisability and integrate qualitative methods like interviews to explore student’s motivation and barriers to entrepreneurial intention.
Keywords: Entrepreneurial intention; Unemployment; Entrepreneurship; Theory of planned behaviour